2014
DOI: 10.1111/anae.12786
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-regression analysis of mivacurium for tracheal intubation

Abstract: SummaryWe systematically reviewed factors associated with intubation conditions in randomised controlled trials of mivacurium, using random-effects meta-regression analysis. We included 29 studies of 1050 healthy participants. Four factors explained 72.9% of the variation in the probability of excellent intubation conditions: mivacurium dose, 24.4%; opioid use, 29.9%; time to intubation and age together, 18.6%. The odds ratio (95% CI) for excellent intubation was 3.14 (1.65-5.73) for doubling the mivacurium do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Since analysis by quality rather than clinical characteristics is properly termed ‘sensitivity’ analysis rather than ‘subgroup’ analysis, this suggests that the terminology was incorrectly applied by some authors. Twenty reported a change in pooled effect size over a range of clinically relevant outcomes due to the influence of low methodological quality/high risk of bias studies (Table S1). Some showed that low methodological quality/high risk of bias studies decreased the apparent incidence of adverse events such as mortality, infection or requirements for increased blood transfusion .…”
Section: Resultsmentioning
confidence: 99%
“…Since analysis by quality rather than clinical characteristics is properly termed ‘sensitivity’ analysis rather than ‘subgroup’ analysis, this suggests that the terminology was incorrectly applied by some authors. Twenty reported a change in pooled effect size over a range of clinically relevant outcomes due to the influence of low methodological quality/high risk of bias studies (Table S1). Some showed that low methodological quality/high risk of bias studies decreased the apparent incidence of adverse events such as mortality, infection or requirements for increased blood transfusion .…”
Section: Resultsmentioning
confidence: 99%
“…Such sequential methods can provide information on when firm evidence is reached in a cumulative meta-analysis, and can also provide an early clue to the lack of presence of a clinical effect. Finally, the systematic review can cast light on other aspects of practice; within Anaesthesia we have recently published a systematic review with meta-regression [32], a review of the interaction between ondansetron and tramadol [33], and case reports and series of cranial nerve injuries with supraglottic airways [34]. Manipulation of the existing dataset from a systematic review also helped confirm a recent case of research fraud [35].…”
Section: Newer Developmentsmentioning
confidence: 99%
“…Random‐effects meta‐regression analysis demonstrated that, within the age range 0‐12 years, excellent intubation conditions for rocuronium (17 study arms, 326 participants, R 2 = 71.4 and I 2 = 26.8%) were more likely with higher NMBA dose, younger participants and increasing time to intubation (Figure , Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Each circle represents a treatment group, the diameter of which is proportional to the number of participants. Some of the treatment groups are not displayed as they are overlapped by others…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation